Pendampingan penggunaan pemrograman Python untuk penyelesaian soal geometri ruang - Junianto; Muh Wildanul Firdaus; Katon Agung Ramadhan; Aulia Fonda; Mus’ab Abdul Aziz (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2026)
The purpose of this community service program is to train eighth-grade junior high school students to use Python 3.13.2 programming language to solve volume problems in geometric shapes. The Python mentoring program was conducted at Muhammadiyah 9 Junior High School, Yogyakarta, and was attended by 29 eighth-grade students. The program was conducted through several stages, namely planning, preparation, implementation, and evaluation. The results show that this mentoring had a positive influence on students' abilities and interest in mathematics learning technology. Students also learned coding using the Python 3.13.2 computer programming language. Based on the post-mentoring questionnaire results, 95% of the students reported becoming more confident and self-assured in using Python for mathematics learning. This mentoring also succeeded in training students' critical thinking and mathematical logic skills. In addition, student participation increased because they did direct practice, not just learning theories.